Kajian kesan suhu terhadap proses pengeringan halwa terung asam dengan menggunakan ketuhar perolakan - Ab Tahir, Aliff; Nik Wan Zainun, Wan Hairilamei; Sukindar, Nor Aiman (Politeknik Kuching Sarawak, 2018)
“Terung Asam” is a very popular fruit-shaped vegetable in Sarawak. “Terung Asam” or “Terung Dayak” also known as “Terung Iban” is a kind of vegetable from the Solanaceae family. The scientific name for “Terung Asam” is Solanum Lasiocarpum Dunal. These vegetables have several nutrients including proteins, vitamin c and iron. “Terung Asam” has received a Geographical Indications (GI) certificate under the Sarawak government through the Malaysian Intellectual Property Corporation (MyIPO). Currently, limited studies are conducted on “Terung Asam”. Therefore, a study is carried out using self-developed convection oven to investigate the effect of temperature on drying process of “Terung Asam” halva. Three temperature levels are used which are 55˚C, 65˚C and 75˚C. The drying process is done so that the moisture content is at 14-17%. The results showed that the moisture content of the samples was 84%. For the next sample, there was a strong correlation between the drying rate and the drying temperature at 55˚C, 65˚C and 75˚C.